Is Immigration Necessary for Italy? Is it Desirable? - Luigi Bonatti (ifo Institute - Leibniz Institute for Economic Research at the University of Munich, 2020)
Italy, together with other Southern European countries, represents an anomaly in the history of modern migration. In the last three decades, the country has attracted a substantial number of migrants while its employment rate has remained structurally low because of a persistently high unemployment rate and its population's low participation to the labor market. This article illustrates some facts in order to escape from the obtuse dispute between anti-immigrant propagandists on one side and a rhetoric of immigrant reception on the other. It shows what this anomaly implies and suggests possible policy options for dealing with it.
Keywords: 330